Green patents: a way to guide the eco-innovation success process?. Issue 2 (3rd June 2019) - Scarpellini, Sabina; Portillo-Tarragona, Pilar; Marin-Vinuesa, Luz Maria
Abstract : Purpose: The purpose of this paper is to explore the determinants of successful eco-innovation processes, using R&D intensity and green patents as metrics for eco-innovation measurement and analysis. Design/methodology/approach: The paper reports the results of a quantitative study based on a sample of 2, 218 firms with proactive profiles in eco-innovation, 249 of which have green patents registered in Spain or in the European Union. Findings: The results suggest positive relationships between the activity of eco-innovation of firms with both the innovation activity in firms and the R&D intensity. The findings also confirm the influence of implementing innovation in the financial performance of business. Research limitations/implications: The results will be useful for future studies on the subject and for practitioners making decisions on investments in collaborative R&D and its protection through industrial property in the form of green patents. The main determinants of eco-innovation analysed in this paper can be directly translated into practices because they provide information on how to strengthen these determinants in environmental R&D investments and the registration of green patents. Practical implications: The results will be useful for future studies on the subject and for practitioners making decisions on investments in collaborative R&D and its protection through industrial property in the form of green patents. The main determinants of eco-innovation analysed in this paper can be directly translated into practices because they provide information on how to strengthen these determinants in environmental R&D investments and the registration of green patents. Originality/value: Despite the popularity and potential impact of the eco-innovation on economy or society, it has fallen short in terms of its potential to improve financial performance in firms. This paper argues that the level of eco-innovation activity explains some variability in financial performance. In fact, those firms that have greater levels of innovation increase their performance. Abstract : Propósito: Explorar los determinantes del éxito de los procesos de ecoinnovación, utilizando la intensidad de I + D y las patentes verdes como indicadores para la medición y el análisis de la ecoinnovación. Diseño/metodología/enfoque: Se analizan y presentan los resultados de una investigación cuantitativa basada en una muestra de 2218 empresas con perfiles proactivos en ecoinnovación, de las cuales 249 tienen patentes verdes registradas en España o en la Unión Europea. Resultados: Los resultados sugieren relaciones positivas entre la actividad de ecoinnovación de las empresas con su actividad de innovación y la intensidad de la I + D. Los resultados también confirman los efectos que la implementación de innovaciones tiene sobre el desempeño financiero de las empresas. Limitaciones/implicaciones de la investigación (si corresponde): La medición de la ecoinnovación es incluso más compleja que la medición de la innovación debido a sus aspectos ambientales intrínsecos. Se podría alcanzar una evaluación más profunda con un mayor número de variables y una muestra más grande. Implicaciones prácticas (si corresponde): Los resultados serán útiles para futuros estudios sobre el tema y para los profesionales que toman decisiones sobre inversiones en investigación y desarrollo en colaboración y su protección a través de la propiedad industrial en forma de patentes verdes. Los principales determinantes de la ecoinnovación analizados en este estudio pueden traducirse directamente a las prácticas, ya que proporcionan información sobre cómo fortalecer estos determinantes en las inversiones en I + D ambiental y el registro de patentes verdes. Originalidad/valor: A pesar de la popularidad y el impacto potencial de la ecoinnovación en la economía o la sociedad, se ha quedado corto en cuanto a su potencial para mejorar el desempeño financiero de las empresas. Este estudio sostiene que el nivel de actividad de ecoinnovación explica cierta variabilidad en el desempeño financiero. De hecho, aquellas empresas que tienen mayores niveles de innovación aumentan su desempeño.